The life cycle of seismite research - Van Loon, A.J. (Tom) (Geologos, 2014)
1. The life cycle of seismite research. 2. Unfortunate childhood. 3. Stage of adolescence. 4. Upcoming stage of maturity. 5. The future: a fully grown-up stage. 6. For now: a new challenge.